2021
DOI: 10.1016/j.jaad.2020.08.113
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with apremilast in hidradenitis suppurativa: A 2-year follow-up of initial responders

Abstract: I 2 ¼ 69.16%; P ¼ .001) compared to nail 2 (ER, 5%; 95% CI, 3-8; I 2 ¼ 65.22%; P ¼ .002), nail 3 (ER, 5%; 95% CI, 3-8; I 2 ¼ 0.00%; P ¼ .83), nail 4 (ER, 5%; 95% CI, 3-8; I 2 ¼ 0.00%; P ¼ .74), and nail 5 (ER, 7%; 95% CI, 3-17; I 2 ¼ 73.02%; P ¼ .001) (Supplemental Fig 4; available via Mendeley at https://doi.org/10.17632/ y6kxmmz9x9.1). Regarding melanomas of individual toes, the distributions were as follows: hallux: ER, 40%; 95% CI, 25-57; I 2 ¼ 0.00%; P ¼ .53); second toe: ER, 17%; 95% CI, 8-33; I 2 ¼ .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 4 publications
0
31
0
Order By: Relevance
“…The mean values of further parameters including pain and itch were also moderately decreased in the apremilast group compared to baseline, while being mostly increased in the placebo group. Of note, there was a decrease in the overall therapy response over the 16 weeks of treatment; 85 nonetheless, a few study responders showed a sustained therapy response in a 1–2 years follow‐up study 86 . While decreasing the cutaneous pro‐inflammatory cytokine production is a clearly reasonable approach for HS, the parallel inducing effect of PDE4 inhibitors on IL‐10, a cytokine which per se is highly abundant in HS skin, should be viewed critically 18,87 .…”
Section: Phosphodiesterase‐4mentioning
confidence: 96%
“…The mean values of further parameters including pain and itch were also moderately decreased in the apremilast group compared to baseline, while being mostly increased in the placebo group. Of note, there was a decrease in the overall therapy response over the 16 weeks of treatment; 85 nonetheless, a few study responders showed a sustained therapy response in a 1–2 years follow‐up study 86 . While decreasing the cutaneous pro‐inflammatory cytokine production is a clearly reasonable approach for HS, the parallel inducing effect of PDE4 inhibitors on IL‐10, a cytokine which per se is highly abundant in HS skin, should be viewed critically 18,87 .…”
Section: Phosphodiesterase‐4mentioning
confidence: 96%
“…For the abscess and nodule count, a significant difference was observed with a mean difference of −2.6 ( p = 0.011). Patients who achieved HiSCR at the end of the study were offered to continue apremilast treatment in a compassionate use program [ 36 ]. Of the eight patients who achieved HiSCR, four discontinued before the first year.…”
Section: Current Biologics and Small Molecules With High Level Evidence For The Indication Hidradenitis Suppurativamentioning
confidence: 99%
“…In their randomized controlled trial, including 20 patients with moderate HS (of which 15 were randomly assigned to apremilast therapy at a dose of 30 mg twice daily and 5 to placebo), Vossen and colleagues reported that, at week 16, 53% (8 out of 15) of patients achieved HiSCR in the apremilast group compared to 0% in the placebo group [ 260 ]. In a 2-year follow-up of initial responders (8 patients), HiSCR at both the 1-year and the 2-year follow-up visits (compared with baseline) was achieved by all 4 patients who continued apremilast treatment [ 261 ]. Weber et al assessed the efficacy of apremilast (30 mg twice a day) in the management of 9 patients (3 females and 6 males) with moderate-to-severe HS (5 of which had previously failed anti-TNF-α therapies).…”
Section: (New Medical) Therapeutical Approaches In Hsmentioning
confidence: 99%